Total Latin American architecture libretto of modern reflections and contemporary works - Brea, Ana de (Actar Publishers, 2016)
A selected, fully open, and deep assemblage, that carries the explicit intent of outlining, conceptual and practical verifications, on critical views and specific projects, concerning the actual architecture in the Latin American territory.